Similar effectiveness of R‐CHOP‐14 and ‐21 in diffuse large B‐cell lymphoma—data from the prospective German Tumour Registry Lymphatic Neoplasms. (4th September 2019) - Knauf, Wolfgang; Abenhardt, Wolfgang; Mohm, Johannes; Rauh, Jacqueline; Harde, Johanna; Kaiser‐Osterhues, Anja; Jänicke, Martina; Marschner, Norbert; ,
Abstract: Objectives: R‐CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone) is the standard therapy for patients with previously untreated diffuse large B‐cell lymphomas (DLBCL). Dose‐dense two‐weekly 'R‐CHOP‐14' was not superior over three‐weekly 'R‐CHOP‐21' in randomised clinical trials (RCTs). We present real‐world data on effectiveness of R‐CHOP‐14 and R‐CHOP‐21 in patients with DLBCL treated in German routine practice. Methods: We identified 582 patients with DLBCL treated with R‐CHOP‐14 or R‐CHOP‐21 in 92 sites from the prospective clinical cohort study Tumour Registry Lymphatic Neoplasms. Patients' schedules were classified by (a) length of the initial first cycle and (b) length of cycles 1‐4. Results: About 55% of patients received R‐CHOP‐21, 45% R‐CHOP‐14, in median 6 cycles. 51% and 55% of patients, respectively, were able to continue their initial R‐CHOP‐14 and R‐CHOP‐21 schedule. While most characteristics between the patient cohorts were similar, patients receiving R‐CHOP‐21 presented slightly more often with tumour stage I and lower IPI risk. 3‐year overall survival of patients with R‐CHOP‐14 and R‐CHOP‐21 did not differ: 84% vs 84% (first cycle), 87% vs 89% (cycles 1‐4). Conclusions: Patients with DLBCL in Germany are slightly more likely to receive R‐CHOP‐21 than R‐CHOP‐14. Both schedules are similarly effective in routine practice confirming the results from RCTs.